Implementation of Blended Learning in Project-Based Learning Models in Vocational Schools in North Sulawesi - Tiwow, Gilly Marlya; Katuuk, Deitje Adolfien; Lengkong, Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree (JR Education, 2023)
Blended learning is a learning model that integrates online and offline learning. This article explains how blended learning can be applied to project-based learning in SMK. This article also discusses the benefits and challenges of implementing blended learning and how teachers can overcome these challenges. This research uses a qualitative descriptive method which is a research method that refers to the collection and analysis of non-numeric data to answer research questions. The results show that blended learning can increase student motivation and participation in project-based learning at SMK. The implementation of blended learning can also facilitate students in developing critical, creative, and collaborative skills needed in the world of work. It is hoped that this article can provide insight and inspiration for vocational teachers in improving the quality of project-based learning through the implementation of blended learning. This study concludes that blended learning can increase student participation in learning, optimize the use of technology, and improve student learning outcomes. This study recommends that the implementation of blended learning can increase student participation and motivation in learning, as well as help students to develop critical thinking skills, creativity, and teamwork.